Perpetuating Stigma: Representation of Widows and Divorcees (Janda) in Indonesian Popular Media - Iwan Awaluddin Yusuf (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
The image of widows or divorcees (janda) has been negatively portrayed in the various forms of Indonesian popular media. Media critics have shown that media representation contributes to the spread of inaccurate and misleading ideas about janda in societies. This paper discusses the representation of widows and divorcees in mainstream Indonesian films, songs, and news coverage. Through qualitative content analysis of selected Indonesian films, dangdut songs, and news coverage using the word “janda” in the title, this study revealed that stigmatisation continues to occur. It found that janda are often depicted stereotypically across film genres. The appearance of janda in Indonesian film is accompanied by its typical attributes, such as “beautiful”, “rich”, “young”, and “seductive”. The negative representation of janda also found in dangdut songs. Through the title and lyrics, those songs often associate janda as inferior, powerless, or conversely, predatory and sexually seductive. News coverage depicting widows and divorcees, which should be based on facts was found to be excessively biased due to the addition of the journalist’s personal opinion.